A study on how the promotional tools used by Cosmopoint International College Of Technology Kota Bharu (CICT KB) give impact to increase student enrollment / Muhd Hazim Shukri - Shukri, Muhd Hazim (2011)
This research was conducted to study the Promotional Tools that Influence Student Enrollment: A case study at Cosmopoint International College of Technology Kota Bharu (CICT KB). The objective of this research is to identify the elements of promotional tools that lead to the student enrollment with the promotional tools done by CICT KB. This study also was conducted to recommend CICT KB on how to increase their student enrollment by using the promotional tools. Besides that, to analyze relationship between independent variables (public relation, publicity and advertisement) is also objective of this study. The researcher had distributed the questionnaire among 100 respondents. Public relation, publicity and advertisement are the independent variables that being selected by the researcher. After collecting the data and analyze it, the result shows that there is association or relationship between these independent variables and the students enrollment. The finding also shows that between independent variables have positive relationships. By conducting this research also, the researcher hopes that CICT KB can improve their promotion tools in order increase students enrolment